Assessment of anti-inflammatory therapy effectiveness in the early postoperative period of cataract surgery - M. M. Bikbov; E. L. Usubov; G. M. Kazakbayeva; A. U. Galimov; N. I. Pokhilko; I. D. Valishin; A. M. Nizamutdinova (Российский офтальмологический журнал)
Purpose: To evaluate the efficacy and safety of nonsteroid anti-inflammatory drugs (NSAIDs) in monotherapy and as part of combination therapy with glucocorticosteroids for the prevention of postoperative inflammation after cataract phacoemulsification.Material and methods. The study included 75 patients who underwent phacoemulsification with implantation of a posterior chamber intraocular lens. Patients were divided into groups depending on anti-inflammatory treatment: A1 — nepafenac (Nepafenac-Optic), A2 — bromfenac (Broxinac), A3 — dexamethasone (Dexamethasone), B1 — Nepafenac-Optic + dexamethasone, B2 — bromfenac + Dexamethasone. Postoperative inflammation was assessed by the severity of conjunctival hyperemia, pain, Tyndall effect and retinal thickness in the macular region.Results. The severity of the pain symptom was lower in the nepafenac group (A1) as compared to groups A2 and A3 by 49 and 74 %, respectively. A strong direct correlation with the Tyndall effect was revealed, which was more pronounced in group A3 and amounted to 0.73 points. An increase in the thickness of the retina in the macular region in the early stages after surgery was observed in groups A2 and A3, on average by 30 microns. In the groups of Nonpafenac Optic and combined therapy with GCS, the thickness of the retina remained stable. Cystic macular edema in the early postoperative period was observed in groups A2 and A3 and amounted to 2.6 and 1.3 %, respectively. There was a tendency to higher IOP rates in the GCS therapy groups.Conclusion. After surgical treatment of cataracts, the Nepafenac Optic significantly relieves the pain syndrome, as compared with monotherapy with bromfenac or dexamethasone. Nepafenac-Optic helps to reduce the severity of inflammation in the anterior and posterior segments of the eye, minimizes the changes in the retinal thickness of the macular region in the postoperative period. The severity of these effects is comparable to the combination therapy of NSAIDs + GCS. Nepafenac-Optic does not increase IOP, has a more favorable safety profile than in combinations with glucocorticosteroids, and reduces the risk of postoperative complications.